Analyzing probability of detection as a function of defect size and depth in pulsed IR thermography; NDT & E International; Vol. 130 - Moskovchenko A. I. Aleksey Igorevich; Svantner M. Michal; Vavilov V. P. Vladimir Platonovich; Chulkov A. O. Arseniy Olegovich (2022, 2022)
Title screen